2018
DOI: 10.7567/jjap.57.041501
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue behavior of resistive switching in a BiFeO3thin film

Abstract: The change of the resistive switching effect in an Au/BiFeO3/SrRuO3 structure under repetitive switching was studied. The current–voltage characteristics indicated space-charge-limited (SCL) conduction. The transition voltage from ohmic to SCL, voltage of the trap-filled limit, and resistance increased with switching cycle number in the wake-up stage. Such changes were attributed to the increase of trap density caused by the release of polarization domains. Ohmic and SCL currents increased with switching cycle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Figure 5(b) compares the I-V curves before and after the abrupt RS transition. It has been reported that the slope of logI versus logV can be used as a criterion for comparison of the distribution of traps [41,46]. A low slope indicates a gradual trap distribution, while a higher slope implies an abrupt one.…”
Section: Analysis Of the Three-state Rs Conduction Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 5(b) compares the I-V curves before and after the abrupt RS transition. It has been reported that the slope of logI versus logV can be used as a criterion for comparison of the distribution of traps [41,46]. A low slope indicates a gradual trap distribution, while a higher slope implies an abrupt one.…”
Section: Analysis Of the Three-state Rs Conduction Mechanismmentioning
confidence: 99%
“…The increase of the slope after the transition indicates that the distribution of traps becomes more and more abrupt compared with the state before the transition. The change of the traps' distribution can be ascribed to the redistribution of oxygen vacancies [46].…”
Section: Analysis Of the Three-state Rs Conduction Mechanismmentioning
confidence: 99%
“…Recently, the reliability issues, such as imprint, fatigue, retention loss, etc., have been intensively investigated in the FE-based technologies. [13][14][15][16][17] However, the time-dependent dielectric breakdown (TDDB) in the FE-based technologies is still lack of investigation. In the previous work, we evaluate the gate leakage current (I G ) and TDDB stability in the FE HfZrO 2 (HZO) on the n-type Ge substrate in the devices with and without in-situ NH 3 plasma interfacial layer (IL) treatment.…”
Section: Introductionmentioning
confidence: 99%
“…The operation principle of a memristor described by the above equations is clear and simple. However, in a real memristive device, the origin for resistance change is complicated, for example, possible mechanisms include migration of anions [3][4][5][6][7] or cations, 8,9) charge trapping and detrapping, [10][11][12][13][14][15] polarization switching in ferroelectrics-composed memristors, [16][17][18][19][20][21][22][23] etc.…”
Section: Introductionmentioning
confidence: 99%